Masks and racial stereotypes in a pandemic: the case for surgical masks. (July 2022) - Christiani, Leah; Clark, Christopher J.; Greene, Steven; Hetherington, Marc J.; Wager, Emily M.
Abstract: To contain the spread of COVID-19, experts emphasize the importance of wearing masks. Unfortunately, this practice may put black people at elevated risk for being seen as potential threats by some Americans. In this study, we evaluate whether and how different types of masks affect perceptions of black and white male models. We find that non-black respondents perceive a black male model as more threatening and less trustworthy when he is wearing a bandana or a cloth mask than when he is not wearing his face covering—especially those respondents who score above average in racial resentment, a common measure of racial bias. When he is wearing a surgical mask, however, they do not perceive him as more threatening or less trustworthy. Further, it is not that non-black respondents find bandana and cloth masks problematic in general. In fact, the white model in our study is perceived more positively when he is wearing all types of face coverings. Although mandated mask wearing is an ostensibly race-neutral policy, our findings demonstrate the potential implications are not.